1989
DOI: 10.3109/00207458908986227
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Evoked Potential Changes During Muscle Testing

Abstract: Fifteen naive subjects with no known neurological problems were tested by means of manual muscle testing to determine two "strong" and one "weak" muscle on a limb contralateral to the stimulated side. Somatosensory evoked potentials (SEP) were then recorded from contralateral median nerve stimulation while a naive tester tested the three previously identified muscles. In all subjects the baseline (no muscle test) and control "strong" muscle test recordings were comparable while the recording from the "weak" mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Although the mechanism of action is disputed, previous research has established that there is a significant difference between ''strong'' muscles and ''weak'' muscles during a muscle test [3,[21][22][23][24][25]. Therefore, the objective of this study in not to assess if there is a difference, but instead, to estimate how widespread is the use of kMMT.…”
Section: The Kinesiology-style Manual Muscle Testmentioning
confidence: 91%
“…Although the mechanism of action is disputed, previous research has established that there is a significant difference between ''strong'' muscles and ''weak'' muscles during a muscle test [3,[21][22][23][24][25]. Therefore, the objective of this study in not to assess if there is a difference, but instead, to estimate how widespread is the use of kMMT.…”
Section: The Kinesiology-style Manual Muscle Testmentioning
confidence: 91%
“…This effect has been observed as muscle testing responses which vary from the predicted normal patterns (Leisman et al, 1989). This deviation from normal is thought to consist of alterations in patterns of facilitation and inhibition of muscles.…”
Section: Normal Gait Patterns Observed With Manual Muscle Testingmentioning
confidence: 94%
“…In an earlier paper, Leisman et al (1989) also identified differences in somatosensory evoked potentials (SSEPs) recorded during the testing of conditionally facilitated versus conditionally inhibited muscles. SSEPs were recorded from the contralateral median nerves of fifteen subjects while three Int J Neurosci Downloaded from informahealthcare.com by Technische Universiteit Eindhoven on 11/17/14 For personal use only.…”
Section: Muscular Facilitation and Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscles in this study were tested according to the method outlined in the texts by Walther, Kendall, and Daniels and Worthingham (Kendall et al, 2005;Daniels and Worthingham, 2002;Walther, 2000). This method of MMT has been previously investigated in numerous reliability studies (Jepsen et al, 2004;Bohannon, 2001;Caruso and Leisman, 2000;Lawson and Calderon, 1997;Kelly et al, 1996;Hsieh and Phillips, 1990;Leisman et al, 1989;Wadsworth et al, 1987;Iddings et al, 1961).…”
Section: Introductionmentioning
confidence: 97%